Evaluation of Modified Advanced Locking Plate System by MIPO and ORIF Techniques for Tibial Fracture Repair in Dogs - Pooja, Hanchinamne Shivamurthy; Desai, Dilipkumar; Patil, Manjunath (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The study was conducted on 12 clinical cases of dogs with tibial fractures, which were randomly divided into two groups consisting of six dogs in each group. In group I (n=6), fractures were repaired by minimally invasive plate osteosynthesis (MIPO) using 3.5 mm modified advanced locking plate system (ALPS) with a plate width of 10 mm and in Group II (n=6), fractures were repaired by open reduction and internal fixation (ORIF) techniques using 3.5 mm modified advanced locking plate system with a plate width of 10 mm. Based on clinical, biochemical and radiological evaluation, the healing of the fracture was studied at intervals of 0, 15th, 30th, and 60th post-operative days. Both groups underwent clinical evaluations of weight bearing, functional limb usage and lameness grading at particular interval. On clinical observations of weight bearing (functional outcome and lameness grading), dogs treated with MIPO showed early weight bearing compared to ORIF technique. The biochemical parameters obtained on the 0, 15th, 30th and 60th day showed a fluctuating trend. However, values were within the normal physiological limit. Post-operative radiographic evaluation showed progressive healing of fracture site with lesser callus formation in group I compared to group II. Post-operation complication of plate bending observed in one case on 5th day and wound dehiscence in two dogs of group II. In conclusion, both techniques with modified ALPS provided adequate stability and immobilisation of fracture fragments, allowing early ambulation with tibial fractures, whereas MIPO technique provides early functional outcome of the fractured limb with less post-operative complication than open reduction technique.